Biomimetic lipid–fluorescein probe for cellular bioimaging - Moon, Hyungkyu; Sultana, Tania; Lee, JeongIk; Huh, Jungrim; Lee, Hae Dong; Choi, Myung-Seok (Frontiers in Chemistry, 2023)
Tracking the morphology of cellular membranes is of great importance for biological research. Here, three phospholipid-mimicking fluorescent probes (FP1–FP3) comprising fluorescein and two lipophilic groups of saturated and/or unsaturated C18 fatty acids were synthesized, and their optical properties in protic solvent were investigated. Like in biological phospholipids, the fluorescein group acts as a hydrophilic polar headgroup and the lipid groups act as hydrophobic non-polar tail groups. In live cell experiments on canine adipose-derived mesenchymal stem cells, all three probes localized to the cellular membrane, as confirmed by confocal laser scanning microscopy. Flow cytometry analysis demonstrated that FP3, which contains both saturated and unsaturated fatty acids, had the largest cellular uptake and strongest fluorescence intensity. The biomimetic nature of these molecules means they are highly compatible with the unique structure of the phospholipid bilayer of cell membranes, facilitating their use as fluorescent probes for cellular bioimaging.